Challenges and Emerging Perspectives of Quality Assurance and Teacher Education in Nigerian Universities: A Literature Review - Imhangbe Osayamen S.; Oviawe Jane I.; Aluede Oyaziwo; Obinyan Gabriel; Oke Tunde Dayo (De Gruyter, 2023)
Education plays a critical role in the effective pursuit and attainment of overall growth and technological advancement of any country. Thus, if Nigeria as a nation is to achieve competitive growth and technological advancement, the quality and type of her educational system must not only be right but also carefully sustained. If an improved quality of education in the country must be attained and sustained, the quality of her teacher education must be equally enhanced. The quest, therefore, for a sustained high-quality teacher education in Nigeria will not yield positive results; there is no corresponding functional and effective quality assurance (QA) and control mechanism in place. It is against this backdrop that this article reviewed QA mechanisms and approaches in place for the delivery of high-quality teacher education in Nigerian universities, the challenges, and emerging perspectives. It noted, however, that their functionality and productivity in terms of yielding the desirable impact were diminished by a myriad of challenges. The article then proposed an overhaul of the existing QA mechanisms while advocating that educational management and Nigerian authorities on teacher education must insist on acceptable standards and monitor performance to guarantee QA.